SWOC (Strengths, Weaknesses, Opportunities, Challenges) Analysis of Child Malnutrition Treatment Centre (CMTC), Mahuva Block, Surat District - Patel, Manan J; Patel, Prakash B; Bansal, R K (National Journal of Community Medicine, 2014)
Introduction: Child Malnutrition Treatment Centre (CMTC) provide nutritional therapy to severe malnourished children. The objective of the study is to evaluate Strengths, Weaknesses, Opportunities and Challenges (or Threats) of Community Malnutrition Treatment Centre (CMTC), Mahuva. Methodology: Out of 3 functioning CMTCs in Surat district, CMTC Mahuva was randomly selected & SWOC (Strengths, Weaknesses, Opportunities and Challenges) analysis of the centre was done by interviewing superintendent, nutritionist, other staff of centre and beneficiaries’ mothers. Results: CMTC Mahuva having strengths such as definite guidelines, motivated and trained human resource and financial resource, good infrastructure, support by Superintendent of CHC Mahuva. Weaknesses like insufficiency of budget, non-availability of pediatrician in nearby place and lack of fully functioning Nutritional Rehabilitation Centre at district level also co-exist. Centre is having external opportunities like use of Rogi Kalyan Samiti funds for purchase of medicine, use of CM-SETU (Chief Minister, Services of Experts at Treatment Unit) for availing pediatrician’s services, pooling of medicines supplied to other health centres, donations from private companies etc. Challenges like beneficiaries referred but not reaching to centre due to social reasons, impossibility of night stay at centre, issues of drop out, child enrolled without any companion are also present. Conclusion: Even though CMTC, Mahuva is having some internal weaknesses and external challenges, the existing staffs are very enthusiastic and trying their best to achieving the objectives by balancing these weaknesses and challenges with the help of existing strengths and opportunities.